CAROB POWDER AND ITS POTENTIAL APPLICATIONS IN EDIBLE BIOPOLYMERS - BASED FILMS FOR FOOD INDUSTRY PACKAGING - ROXANA PUSCASELU *, SONIA AMARIEI; ROXANA PUSCASELU *, SONIA AMARIEI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The aim of the present research was to develop a new packaging material for powdered food products, such as instant beverages or dried vegetables, enriched with carob powder. Due to its proprieties can successfully replace cacao, and can be consumed by both adults (with or without special needs), but also by children. Packaging made from biopolymers is completely edible and can be consumed with the product which contain due to its full solubility in hot water (30 seconds maintaining in water at 80 ºC). The addition of carob into the film composition has improved the physical and mechanical properties of the control samples (without carob powder). The obtained results successfully qualify these materials for use as food packaging material and not only.